2023
DOI: 10.1029/2023gl103812
|View full text |Cite
|
Sign up to set email alerts
|

Mega Forest Fires Intensify Flood Magnitudes in Southeast Australia

Abstract: Wildfires are uncontrolled fires that usually occur during severe droughts and/or heatwaves. In contrast to controlled, prescribed fires, wildfires can directly cause billions of dollars in damage to properties and ecosystems, and indirectly affect the carbon cycle and climate (Godfree et al., 2021;Loehman, 2020;Moritz et al., 2014). With changes in vegetation and soils, wildfires can also affect hydrological processes. Over short periods of time, they may reduce forest water use by the large loss of vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…This is consistent with site-based investigations that found that the largest post-wildfire floods (28) were generated by infiltration-excess runoff from high-intensity rainfall. It is also congruent with recent regional analysis in Australia showing that the largest post-wildfire floods are generated by infiltration-excess runoff mechanisms (9). However, our analysis also suggests that relatively large post-wildfire floods may be generated by other streamflow generation mechanisms, such as saturation-excess overland flow and subsurface storm flow, or mixtures of streamflow generation mechanisms, especially in basins >1000 km 2 (Fig.…”
Section: Insight Into Post-wildfire Flood Generation Mechanismssupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with site-based investigations that found that the largest post-wildfire floods (28) were generated by infiltration-excess runoff from high-intensity rainfall. It is also congruent with recent regional analysis in Australia showing that the largest post-wildfire floods are generated by infiltration-excess runoff mechanisms (9). However, our analysis also suggests that relatively large post-wildfire floods may be generated by other streamflow generation mechanisms, such as saturation-excess overland flow and subsurface storm flow, or mixtures of streamflow generation mechanisms, especially in basins >1000 km 2 (Fig.…”
Section: Insight Into Post-wildfire Flood Generation Mechanismssupporting
confidence: 91%
“…4C). This finding is supported by small hillslope studies in burned basins that observed streamflow generation from the saturation-excess mechanism ( 44 , 45 ), regional studies in Australia that indicated post-wildfire saturation-excess runoff generation ( 9 ), and observed increases in shallow and deep subsurface streamflow from groundwater contributions ( 46 ). Modeling frameworks designed to predict the full spectrum of flood magnitudes following wildfire, rather than just the largest floods, may need to incorporate the full spectrum of streamflow generation mechanisms to predict post-wildfire floods, not just the infiltration-excess mechanism.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Another example of combination of reasons is given by fire-flood interactions. In 2019/2020, wildfires ravaged ecosystems and settlements in Australia after a severe drought, which reduced surface infiltration capacity and intensified flooding and erosion, resulting, among other things, in siltation of Sydney's main water supply reservoirs (Kemter et al, 2021, Xu et al, 2023.…”
Section: Combined and Concurrent Reasonsmentioning
confidence: 99%